Dynamics of global and segmental strain as a marker of right ventricular contractility recovery in patients after COVID-19 pneumonia - N. E. Shirokov; E. I. Yaroslavskaya; D. V. Krinochkin; N. A. Osokina (Российский кардиологический журнал)
Aim. To study the changes of morphological and functional right ventricular (RV) parameters depending on the severity of coronavirus infection 2019 (COVID-19) pneumonia over long-term follow-up.Material and methods. A total of 200 patients (men, 51,5%, mean age, 51,4±10,9 years) were examined at 2 control visits (3, 12 months after receiving two negative polymerase chain reaction tests). Patients were divided into following groups: group I (n=94) — lung tissue involvement ≥50% according to inhospital chest computed tomography (chest CT), group II (n=106) — lung tissue involvement˂50% according to chest CT.Results. The groups were comparable in key clinical and functional parameters 3 months after COVID-19 pneumonia. Speckle tracking echocardiography (STE) revealed a significant increase in following global longitudinal strain (LS) parameters: RV free wall endocardial LS (-22,7±3,2% and -24,3±3,8% in group I, p<0,001; -23,2±3,5% and -24,5±3,4% in group II, p><0,001), and RV endocardial LS (-21,0±3,1% and -22,5±3,7% in group I, p><0,001, -21,5±3,2% and -22,6±3,3% in group II, p=0,001 ). Significant increase of segmental endocardial LS was revealed in group I in the basal segments of RV free wall (-26,2±5,1% and -28,1±5,1%, p=0,004) and interventricular septum (IVS) (-16,2 [13,9; 19,5]% and -17,5 [14,6; 21,4]%, p=0,024), IVS middle segment (-20,3±4,1% and -21,5±4,8%, p=0,030), as well as in group II in the apical segments of RV free wall (-21,9±6,7% and -24,4±5,2%, p=0,001) and IVS (-23,7±4,7% and -24,9±4,8%, p=0,014). Conclusion. Recovery of RV function during a 12-month follow-up period in patients with both severe and moderate/mild lung involvement in COVID-19 was detected using the STE method.>˂0,001; -23,2±3,5% and -24,5±3,4% in group II, p˂0,001), and RV endocardial LS (-21,0±3,1% and -22,5±3,7% in group I, p˂0,001, -21,5±3,2% and -22,6±3,3% in group II, p=0,001 ). Significant increase of segmental endocardial LS was revealed in group I in the basal segments of RV free wall (-26,2±5,1% and -28,1±5,1%, p=0,004) and interventricular septum (IVS) (-16,2 [13,9; 19,5]% and -17,5 [14,6; 21,4]%, p=0,024), IVS middle segment (-20,3±4,1% and -21,5±4,8%, p=0,030), as well as in group II in the apical segments of RV free wall (-21,9±6,7% and -24,4±5,2%, p=0,001) and IVS (-23,7±4,7% and -24,9±4,8%, p=0,014).Conclusion. Recovery of RV function during a 12-month follow-up period in patients with both severe and moderate/mild lung involvement in COVID-19 was detected using the STE method.